Karakteristik Kuta Bataguh di Kapuas, Kalimantan Tengah - nfn Sunarningsih; nfn Hartatik; Ida Bagus Putu Prajna Yogi; Unggul Prasetyo Wibowo; Nugroho Nur Susanto; Restu Budi Sulistiyo (Berkala Arkeologi, 2020)
Kuta Bataguh is administratively located in Bataguh and East Kapuas Districts, Kapuas Regency, Kalimantan Tengah. The research aims to reconstruct the characteristics of Kuta Bataguh. This research is using interpretive-descriptive method with the inductive reasoning. Data collection used surveys, excavations, interviews, and literature study. The analysis included environmental, stratigraphic, artifactual, spatial, and absolute dating analysis. Survey (surface and aerial) and excavation activities were carried out inside and outside the fence, both downstream and upstream of the Karinyau River. The results illustrate that the characteristics of Kuta Bataguh are a large permanent settlement that is split by a river. The fortified settlement of Kuta Bataguh was the leader residence of Ngaju community group (as the center of power). By referring to the pattern, function and extent of this settlement, it can be assumed that the local authorities in Bataguh are on par with early state in their socio-political organization.